The impact of technological innovation in promoting marketing strategies-a review paper - Yousef A. Baker, El-Ebiary; Wan Mohd Amir Fazamin, Wan Hamzah; Syarilla Iryani, A. Saany (2020)
Advertising and marketing with revolutionary technology is of specific significance at this second. marketing, method, plans of movement, improvement is vital each from a hypothetical and administrative perspective. the internet has reformed the marketing strategy, interfacing capability customers to corporations in a direction at no different time achievable. records and verbal exchange technologies transformed right into a step by step requirement for anyone at this second. internet advertising offers large, Purposeful route on how groups can get the most out of the net to meet their promoting targets. the business now is predicated on upon the front line groups, for instance, amazon, eBay, YouTube, fb and so forth. an alternate of advertising is in progress as we invest extra time in our smartphones, capsules and transportable desktops to diverse price assessment sites, net seek gear, and lots of social networking websites. the check for brands is to interface with customers through each such a device constantly and make battles that paintings crosswise over web-based social networking and internet commercial enterprise. the real-time websites and portable applications have modified the way of advertising. the modern advertising and marketing division desires to sign up for the inventive facet of the educate – utilizing effective money owed to take gain of individuals' desires and yearnings – with the specialised side of data and analytics. this subject matter will make clear new technological and modern techniques for speaking to the customers and moreover assist people to comprehend superior advertising and marketing in this present truth.